EVALUASI SISTEM MANAJEMEN USAHA PEMBIBITAN SAPI BALI TERINTEGRASI DENGAN PERKEBUNAN KELAPA SAWIT DI KABUPATEN PASAMAN BARAT, PROVINSI SUMATERA BARAT - Bagus Dimas Setiawan; Arfa’i Arfa’i; Yuliaty Shafan Nur (JURNAL ILMIAH PETERNAKAN TERPADU, 2019)
The research objective was to evaluate: 1) Implementation of integration of Bali cattle and oil palm plantations; 2) Obstacles faced in implementing the integration of Bali cattle with oil palm plantations. The study was conducted in Pasaman Barat District, which received assistance of fund from Directorate General of Animal Husbandry in 2012 in the project of integration of beef cattle with oil palm plantation. The method used were survey method, direct observation and using questionnaire. Respondents involved were members of farmer-group who carried out the integration of Bali cattle and palm oil plantation program as many as 56 people from four groups. Data was analyzed using descriptive analysis and comparing the results obtained with the objectives of the integration program itself. The results showed that the effort to integrate Bali cattle with oil palm plantation business was not optimal. The feedstuff given to cattle were superior grass and field grass originating from oil palm plantations. However, oil palm fronds and leaves have not been utilized, and palm oil industry waste in the form of palm mud, fiber palm oil, and palm kernel meal have not been used optimally as well. Utilization of cattle feces as fertilizer for oil palm plants has been used in several groups, but still in the form of untreated fertilizers. The obstacles faced in implementing this integration system are such as the lack of knowledge of farmers about integration, and the mastery of livestock waste processing technology and waste from oil palm plantations is still low, so that the application of integration has not been optimally carried out. Keywords: Bali Cattle, Integration, Oil Palm Plantation, Pasaman Barat District, Survey Method.